Definitions and engineering classifications of tropical lowland peats - Zulkifley, M.T.M.; Ng, T.F.; Raj, J.K.; Hashim, Roslan; Ghani, A.; Shuib, M.K.; Ashraf, M.A. (2013)
Peat classification methods for engineering purposes and the main factors and aspects of these classification systems are discussed. Among the factors that enter into the classification of tropical lowland peats are the organic content and degree or level of humification (on the von Post scale). The organic content as a percentage of the total content determines whether an organic soil is classified as a slightly organic soil (3-20 organic content), an organic soil (20-75 organic content), or a peat (more than 75 organic content). The ASTM standard method of classifying peat is outlined in the Standard Classification of Peat Samples by Laboratory Testing (ASTM D 4427), which includes the use of the ASTM D 5715 (fiber content by field testing for degree of humification) field test method. The von Post humification test (von Post classification system) involves squeezing the peat and the material that is extruded between the fingers, examining the material, and classifying the soil as belonging to one of ten (H1-H10) humification or decomposition categories. Peats are then further subdivided into fibric or fibrous peats (humification range of H1-H3), hemic or moderately decomposed peats (H4-H6), or sapric or amorphous peats (H7-H10). The classification of organic soil or peat for engineering purposes mainly involves using the ignition test (ASTM D 2974) to determine the organic content or determining the percentage of organic content lost on ignition.